Non-invasive mapping of calculation function by repetitive navigated transcranial magnetic stimulation - Maurer, Stefanie; Tanigawa, Noriko; Sollmann, Nico; Hauck, Theresa; Ille, Sebastian; Boeckh-Behrens, Tobias; Meyer, Bernhard; Krieg, Sandro M. (Brain Structure and Function, 2016)
Concerning calculation function, studies have already reported on localizing computational function in patients and volunteers by functional magnetic resonance imaging and transcranial magnetic stimulation. However, the development of accurate repetitive navigated TMS (rTMS) with a considerably higher spatial resolution opens a new field in cognitive neuroscience. This study was therefore designed to evaluate the feasibility of rTMS for locating cortical calculation function in healthy volunteers, and to establish this technique for future scientific applications as well as preoperative mapping in brain tumor patients. Twenty healthy subjects underwent rTMS calculation mapping using 5 Hz/10 pulses. Fifty-two previously determined cortical spots of the whole hemispheres were stimulated on both sides. The subjects were instructed to perform the calculation task composed of 80 simple arithmetic operations while rTMS pulses were applied. The highest error rate (80 %) for all errors of all subjects was observed in the right ventral precentral gyrus. Concerning division task, a 45 % error rate was achieved in the left middle frontal gyrus. The subtraction task showed its highest error rate (40 %) in the right angular gyrus (anG). In the addition task a 35 % error rate was observed in the left anterior superior temporal gyrus. Lastly, the multiplication task induced a maximum error rate of 30 % in the left anG. rTMS seems feasible as a way to locate cortical calculation function. Besides language function, the cortical localizations are well in accordance with the current literature for other modalities or lesion studies.